Quality of life of preschool children with psychomotor development disorders and their families. Availability of medical care and quality of its provision for this category of patients - S.L. Niankovskyy; A.I. Pushnyk (Zaslavsky O.Yu., 2022)
Background. Improving the quality of life of neurologicaly impaired child and his family is an issue of particular importance. The purpose of the study was to assess the quality of life of children with psychomotor development disorders and their families, the impact on the family of existing psychomotor disorders in children, as well as the availability of medical care and satisfaction with the quality of its provision to this category of patients; to identify the relationship between the calculated indicators of quality of life of children and their families and existing disorders of psychomotor development in children. Materials and methods. The study analyzed the results of the survey of 45 neurologically impaired preschool children's parents. Results. A direct significant correlation of different strength was observed between the scores of the boys, their families and children's neurological pathology. The correlation between the performance of the girls, their families and neurological disorders was mostly unreliable. This study also tested that the averages of the boys and their families were significantly higher than those of the girls in some sections of all questionnaires used. The rates of the children with mental retardation and their families mostly significantly exceeded the values of the children with other nosologies. The inverse correlation of different strength was verified between the indicators in the section The Parent HRQL Summary Score of the PedsQLTM 2.0 Family impact module questionnaire, the Total scores of the PedsQLTM Healthcare Satisfaction Generic Module questionnaire, the values in Psychosocial Health Summary section and the Total scores rates of the PedsQLTM 4.0 Generic Score Scales questionnaire in boys with mental retardation and in all examined boys, as well as in their families and neurological disorders. No correlation was found between the rates of the boys with ADHD and their neurological problems. Conclusions. The presence of direct and inverse reliable correlation of different strength between the average values of the examined boys with psychomotor development disorders, boys with mental retardation, as well as their families and the neurological pathology present in children was established. The correlation between the performance of the girls and their families and the neurological disorders of children in most sections is unreliable. It is necessary to conduct research with a larger number of participants.